PELATIHAN IMPLEMENTASI PLATFORM DIGITAL DRAIVFOOD SEBAGAI STRATEGI PENGEMBANGAN UMKM DAN PENCIPTAAN LAPANGAN KERJA DI DESA MALALA - Amirah; Alfansyah Fathur; Mirayanti Mirayanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Madako Tolitoli, 2025)
This community service activity aims to accelerate economic transformation in Malala Village through collaboration with the digital platform Draiv Food. The primary focus of this activity is empowering Micro, Small, and Medium Enterprises (MSMEs) and creating job opportunities for villagers. During its implementation, local business actors received entrepreneurship training, mentoring in the business digitalization process, and support for wider market access through the Draiv Food application. The results of the DRAIV application socialization have positively impacted the community. Through this activity, the community now realizes and understands the function and benefits of the DRAIV application as a local digital service. In addition, this activity also creates new job opportunities, especially for the younger generation interested in becoming delivery partners or digital entrepreneurs. With support from the village government and relevant officials, the use of DRAIV is further strengthened as an effort to move towards an independent and technology-based village.